Systematic Literature Review on the Impact of Green Manufacturing Implementation on Corporate Sustainability Performance - Thoriq, Ezar Aufa; Asyazilal, Abieta; Putranto, Andre Novia; Hidayati, Retno; Mawardi, Wisnu (Research Horizon, 2024)
This literature review explores the impact of green manufacturing on corporate sustainability performance with green innovation as a mediator. Green manufacturing, characterized by environmentally friendly practices in production processes, has gained significant attention due to its potential to enhance sustainability outcomes. Corporate sustainability performance, encompassing economic, environmental, and social dimensions, is crucial for long-term organizational success and stakeholder value creation. Green innovation, including technological advancements and strategic initiatives towards sustainability, plays a vital role in driving positive environmental impacts and competitive advantages. Understanding the interplay between these factors is essential for firms seeking to integrate sustainable practices into their operations and achieve superior performance in a rapidly evolving global landscape.